Second Trimester Fetal and Maternal Epicardial Fat Thickness in Gestational Diabetic Pregnancies - Yavuz, A.; Akkurt, M. O.; Yalcin, S.; Karakoc, G.; Varol, E.; Sezik, M. (Hormone and Metabolic Research, 2016)
Our aim was to evaluate the association between gestational diabetes mellitus and sonographically measured fetal epicardial fat thickness between 24–28 weeks’ gestation. This was a cross-sectional study that included 40 pregnancies with gestational diabetes mellitus, matched with 40 normal pregnancies with similar maternal age, body-mass index, gestational age, fetal gender, and fetal abdominal circumference on ultrasound. Fetal epicardial fat thickness was measured and recorded during ultrasonography at 24–28 weeks of gestation. Maternal evaluation included measurement of maternal epicardial fat thickness, using echocardiography. Fetal and maternal epicardial fat thickness values were compared across the groups. Ultrasound views of fetal epicardial fat thickness were evaluated independently by 3 perinatology fellows to determine inter- and intra-observer variability. Partial and intraclass correlation analyses were used. Fetal and maternal epicardial fat thickness measurements were moderately correlated (r=0.63). Mean fetal and maternal epicardial fat thickness values were higher in gestational diabetes mellitus pregnancies (p=0.004 and p<0.0001, respectively) compared to controls. Fetal epicardial fat thickness was positively correlated (r=0.43) with postchallenge 2-h glucose values. Inter- and intra-observer agreement was high, demonstrated by strong correlations (r=0.99 and r=0.99, respectively) across fetal epicardial fat thickness measurements of the examiners. Fetuses from gestational diabetes mellitus pregnancies have significantly higher fetal and maternal epicardial fat thickness values compared to nongestational diabetes mellitus pregnancies. Fetal epicardial fat thickness obtained during second trimester fetal anatomy ultrasound may potentially be a reliable indicator for gestational diabetes mellitus. However, clinical validation studies are needed.
Keywords: epicardial fat thickness; fetal echocardiography; gestational diabetes mellitus; insulin resistance